THE EFFECT OF GALLERY WALK STRATEGY ON STUDENTS’ SPEAKING SKILL - Edy Waloyo; Farchati (Dialectical Literature and Educational Journal, 2021)
This research aimed to find out the effect of gallery walk strategy on students’ speaking skill at eleventh-grade students MA Darul Masholeh. The study took 24 students as samples from two classes, that was XI IPA as an experimental class, and XI IPS as control class. It used quantitative analysis which is designed as quasi-experimental. The technique of collecting data is testing that is pre-test and post-test. The result showed that: 1). Students’ speaking skill without applying gallery walk strategy still under the standardized score of the school, that is 64.00. 2). Student's speaking skill by applied gallery walk strategy is improved, and most of them succeed to pass the standardized score of the school, that is 84.00. 3). The effect of gallery walk strategy on students’ speaking skill is a significant influence. The gain between the pre-test and post-test score is 15.64 points. Because the t-test result is t account (9.541)> t table at (df) 22 (2.07387)showed that the significance level (Sig. (2-tailed)) was 0.00 which less than the significance level of 0.05. ), so, Ho is rejected, and Ha is accepted. It means that there is a significant effect of using gallery walk strategy on students’ speaking skill at MA Darul Masholeh in advertisement text at eleventh-grade students of MA Darul Masholeh.